Penggunaan teknik data mining dalam pemilihan pekerja ke program latihan - Hairoddin, bin Sugiman. (Universiti Malaysia Sarawak, UNIMAS, 2004)
Data mining is a technique to assist in decision making. It is a new technique and the IPplication of this method in Malaysia is still at a low level. The data mining technique is widely ~d in the business field mainly to know, predict and plan which may result in the increase of an ~anization's income.